Synthesis of Amorphous SiOx Nanowires and Nanofibers by Thermal Evaporation with Gold as Catalyst - Al-Ruqeishi, Majid.S.; Md Nor, Roslan; Mohd Amin, Yosuff; Al-Azri, Khalifa (Malaysian Journal of Science, 2009)
The growths of SiOx nanostructures (nanowires and nanofibers) on Au-coated n-type-Silicon (100) substrate via thermal evaporation were studied. Based on SVLS growth mechanism, the obtained diameter of the nanowires varies between 13 nm and about 243 nm and the diameter of nanofibers found to be around 8 nm to 30 nm. The SiOx nanowires are 194 nm to several microns in length, but the length of SiOx nanofibers are 50 nm to several microns. It was found that the carbo-thermal reactions played an important role to accomplish the growth.